Influence of attitude on mobile banking acceptance and factors determining attitude of end-users in Ethiopia - A. B. Kejela; Daniel Porath (University of Applied Sciences Mainz, 2021)
As observed in many countries, mobile banking can revolutionize the practice of payment transactions. This is especially true for developing countries, where mobile banking has the potential to open non-cash banking services to the unbanked. However, unlike in countries like Kenya and Ghana, in Ethiopia, people still seem to be reluctant to use mobile banking, despite existing platforms availed by Ethiopian commercial banks like Dashen Bank and United Bank. In this paper, we explore the reasons for such reluctance with the help of the technology acceptance model (TAM) and modifications proposed by the literature that are particularly adequate for developing countries and mobile banking: the theory of trying (TT) and the concept of attitude strengths. In our sample of 394 mobile banking subscribers of Dashen Bank and United Bank, we find that a person's attitude is key for the acceptance of mobile banking and that attitude can be best explained by combining the elements of TT with the TAM. As a consequence, to foster mobile banking in Ethiopia, banks are advised to improve potential users' attitude, especially, taking into account the users' learning process and the systems' ease of use.
Keywords: 330; Mobile banking; Technology acceptance model; User acceptance; Theory of trying; Attitude strength; Ethiopia; Structural equation model